257 CORRELATES OF VASCULAR STRUCTURE AND FUNCTION MEASURES IN ASYMPTOMATIC YOUNG ADULTS: THE BOGALUSA HEART STUDY. (1st January 2006) - Bhuiyan, A. R.; Srinivasan, S. R.; Chen, W.; Paul, T. K.; Berenson, G. S.
Abstract : Background: Adverse changes in arterial structure and function, independent predictors of cardiovascular (CV) disease morbidity and mortality, are known to be associated with CV risk factors, especially in middle-aged and older adults. Although noninvasive studies in this regard are beginning to emerge in a younger age population, information is lacking on the correlates of measures of vascular structure and function obtained simultaneously by different noninvasive methods. Methods: In 518 black and white subjects (72% white, 44% male) aged 27 to 43 years, vascular structure and function were measured in terms of (1) carotid artery intima-media thickness (IMT), (2) aorta-femoral pulse wave velocity (af-PWV), and (3) pulsatile arterial function in terms of large (C1) and small (C2) artery compliances. Results: Blacks vs whites and males vs females had higher carotid IMT; blacks vs whites higher af-PWV; and blacks vs whites and females vs males lower C1 and C2. In a multivariate regression model, significant predictors in the order of entry into the model were systolic blood pressure, male gender, age, cigarette smoking, and LDL cholesterol for carotid IMT (R 2 = .189); systolic blood pressure, homeostasis model assessment of insulin resistance (HOMA-IR), cigarette smoking, and age for af-PWV (R 2 = .200); systolic blood pressure, female gender and HOMA-IR for C1 (R 2 = .258); and systolic blood pressure, female gender, age, diastolic blood pressure, cigarette smoking, triglycerides, and black race for C2 (R 2 = .394). Conclusion: In asymptomatic young adults, CV risk factors influence adversely measures of both structure and function of the vasculature to varying degrees, with small artery compliance showing maximum variance. As part of preventive cardiology, assessment of structure/function measures of the vasculature by simple noninvasive methods may be helpful in identifying early vascular damage in a high-risk young population group.